2018
DOI: 10.1103/physrevlett.120.211602
|View full text |Cite
|
Sign up to set email alerts
|

QCD Axion Dark Matter with a Small Decay Constant

Abstract: The QCD axion is a good dark matter candidate. The observed dark matter abundance can arise from misalignment or defect mechanisms, which generically require an axion decay constant f a ∼ Oð10 11 Þ GeV (or higher). We introduce a new cosmological origin for axion dark matter, parametric resonance from oscillations of the Peccei-Quinn symmetry breaking field, that requires f a ∼ ð10 8 -10 11 Þ GeV. The axions may be warm enough to give deviations from cold dark matter in large scale structure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 90 publications
1
103
0
Order By: Relevance
“…The initial (homogeneous) field value in our observable Universe can simply correspond to the initial misalignment of the field away from the vacuum, or it can arise "stochastically" [36][37][38][39][40][41] from the accumulated effect of fluctuations during a long phase of inflation. Additional contributions may arise from production via inflationary fluctuations [42][43][44][45][46][47] as well as from decays of precursor particles [48][49][50][51][52][53]. Modifications to the usual misalignment mechanism have been for example explored in [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…The initial (homogeneous) field value in our observable Universe can simply correspond to the initial misalignment of the field away from the vacuum, or it can arise "stochastically" [36][37][38][39][40][41] from the accumulated effect of fluctuations during a long phase of inflation. Additional contributions may arise from production via inflationary fluctuations [42][43][44][45][46][47] as well as from decays of precursor particles [48][49][50][51][52][53]. Modifications to the usual misalignment mechanism have been for example explored in [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that over a limited range IAXO will have sensitivity to the masses of KSVZ axions. Some new theoretical predictions propose that this range of axion masses could be of importance in describing both inflation and dark matter [29][30][31][32][33]77]. Therefore IAXO, as well as being simply a search for solar axions, may additionally prove valuable in the search for dark matter, and a companion to future haloscopes searching in the same range [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the range of masses accessible to a helioscope, the QCD axion is generally associated with being a subdominant DM component in the simplest cosmologies. Although given the uncertainties, it could in fact easily account for all of it in both the postinflationary [29][30][31][32], and preinflationary scenarios [33,34]. Furthermore there are long-standing astrophysical anomalies for which an axion in this range has been shown to be a viable explanation [35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Arxiv:181109290v2 [Hep-ph] 20 Feb 2019mentioning
confidence: 99%
“…We stress that quantum tunneling plays an essential role here. Indeed, the fluctuation cannot grow if there exists only one minimum, which is in contrast to the axion particle production via parametric resonance due to oscillating coherent axion field [23][24][25][26].…”
Section: Coherent Axion Fieldmentioning
confidence: 98%